Model Inkubasi Bisnis UMKM Berbasis Wakaf Uang Dengan Skema Akad Musyarakah - Mohamad Ainun Najib Zamahsyari (Badan Wakaf Indonesia, 2022)
This study describes a model of community empowerment through the integration of MSMEs and nadzir in utilizing waqf funds and an equitable distribution of business results productivity with Musyarakah contract cooperation. The research method used is a qualitative method by providing a conceptual model or framework and the data sources used are secondary data through a Systematic Literature Review, scientific articles, and survey results conducted by government and private institutions.with an object that focuses on cash waqf as capital to develop MSMEs Business with the Musyarakah Contract scheme. This research can be used as material for improvisation and innovation of models for distributing cash waqf investment results through a business incubation program with a musyarakah contract scheme as a ratio result for everyone involved in business management and cash waqf distributors.